Printing Defects Analysis of Dry Toner Based Digital Print Engines for Plastic Substrates - Chaman Chaudhary, Satish, Bijender (International Journal of Advanced Science and Technology, 2020)
Dry toner-based digital print engines are commonly used for commercial printing all over the world and the dry toner based print engines also have the capability to print plastic substrates. There are a number of printing defects that occur while printing with dry toner-based digital print engines such as faint print, no data is printed, printed in jet black or all over in color, the image is obscured and the dirty background uneven gross, uneven density and lines occurred on an image. Faint print and lines that occurring on an image are the most common printing defects that occur while printing on plastic substrates with dry toner-based digital print engines. The dirty background and the uneven gross are the least occurring defects. These defects usually occur due to some technical problems which can be solved easily.